School meals in the UK: ultra-processed, unequal, and inadequate - Parnham,J; Millett,C; Vamos,E (Public Health Nutrition, 2023)
Recent research paints an alarming picture of the school food system in the UK. This commentary discusses the issues that undermine healthy school meals and considers the actions required to ensure the school food system can meet the challenges ahead.